Disseminated Pyrazinamide-Resistant Mycobacterium Bovis in an AIDS Patient: The Role of Molecular Diagnosis and Optimized Therapy - Fang Y; Wang F; Ji J; Jia H; Ren M; Zheng L; Jia L; Guo C; Wang W; Jiang T; Zhang T (Infection and Drug Resistance, 2025)
Yuan Fang,* Fuchun Wang,* Jiahao Ji,* Han Jia, Meixin Ren, Luyao Zheng, Lin Jia, Caiping Guo, Wen Wang, Taiyi Jiang, Tong Zhang Center for Infectious Diseases, Beijing Youan Hospital, Capital Medical University, Beijing, 100069, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tong Zhang, Center for Infectious Diseases, Beijing Youan Hospital, Capital Medical University, 8 Xitoutiao, Youanmenwai, Fengtai District, Beijing, 100069, People’s Republic of China, Email zt_doc@ccmu.edu.cn Taiyi Jiang, Center for Infectious Diseases, Beijing Youan Hospital, Capital Medical University, 8 Xitoutiao, Youanmenwai, Fengtai District, Beijing, 100069, People’s Republic of China, Email jtyii2004@126.comAbstract: Disseminated Mycobacterium bovis (M. bovis) infection is a rare but serious complication in immunocompromised individuals, particularly in those with advanced HIV/AIDS. Diagnosis is often delayed owing to overlapping clinical features with those of other mycobacterial infections. We report a case of disseminated M. bovis infection in a severely immunocompromised patient with AIDS. Rapid identification was achieved using molecular diagnostic techniques, specifically fluorescent PCR melting curve analysis, which enabled timely adjustments to antimicrobial therapy. The patient showed significant clinical improvement and resolution of symptoms. This case underscores the importance of early molecular diagnostics and tailored therapeutic strategies for managing opportunistic infections, such as M. bovis, in patients with HIV/AIDS. These findings highlight the need for broader implementation of advanced diagnostic tools to improve outcomes and mitigate the risks of treatment failure and drug resistance in vulnerable populations.Keywords: M. bovis, PZA-resistant, AIDS, opportunistic infection, co-infection